The Political Thought of Justice Antonin Scalia: A Hamiltonian on the Supreme Court - Staab, James B. (Rowman & Littlefield Publishers, 2006)
The Political Thought of Antonin Scalia: A Hamiltonian on the Supreme Court traces Justice Antonin Scalia's jurisprudence back to the political and constitutional thought of Alexander Hamilton. Not only is there substantial agreement between these two men in the areas of constitutional interpretation, federalism, separation of powers, executive and judicial power, but the two men also have similar temperaments: bold, decisive, and principled. By examining the congruence in thought between Hamilton and Scalia, it is hoped that a better and deeper understanding of Justice Scalia's jurisprudence will be achieved. While an abundance of scholarship has been written on Justice Scalia, no one has systematically examined his political philosophy. This book also draws out the important differences between Justice Scalia's jurisprudence and that of the other conservative members of the Court_the late Chief Justice William Rehnquist and Justices Sandra Day O'Connor, Anthony Kennedy, and Clarence Thomas.